IDENTIFY MISCONCEPTION ON REACTION RATE CONCEPT USING FOUR-TIER MULTIPLE CHOICE (4TMC) DIAGNOSTIC TEST INSTRUMENT - Ilham Pradana Putra Harahap; Dian Novita (JCER (Journal of Chemistry Education Research), 2021)
Abstract. The aims of this study to identify  the profile of students  conseptions and misconceptions on the concept of reaction rate using a four-tier multiple choice diagnostic test instrument reported in the form of misconception profiles consisting of students' conceptions, students' misconceptions and the causes of misconceptions experienced by students. Based on the results of the study shown (1) the students conception profile is as much as 78% understand the concept, 21% misconceptions and 1% do not understand the concept, (2) the profile of students misconceptions in each sub-material that misconceptions on sub-material of concentration 16%, temperature 19%, surface area 41% and catalyst 24% and as many as 1 student (3%) including the high misconception category, 22 students (67%) included in the medium misconception category and 10 students (30%) were in the low misconception category. Students misconceptions vary in different causes such as; associative thinking 59%, preconceptions 25%, incomplete resoning 13%, humanistic thinking 2% and incorrect intuition 1% .  Keywords: four-tier multiple choice, misconception, reaction rate